2014
DOI: 10.1186/s12870-014-0343-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an osmotin-like protein from Solanum nigrumconfers drought tolerance in transgenic soybean

Abstract: BackgroundDrought is by far the most important environmental factor contributing to yield losses in crops, including soybeans [Glycine max (L.) Merr.]. To address this problem, a gene that encodes an osmotin-like protein isolated from Solanum nigrum var. americanum (SnOLP) driven by the UBQ3 promoter from Arabidopsis thaliana was transferred into the soybean genome by particle bombardment.ResultsTwo independently transformed soybean lines expressing SnOLP were produced. Segregation analyses indicated single-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Recently we have cloned and characterized a new OLP gene from Solanum nigrum ( SindOLP , BankIt 1588324 Solanum KC292261), which exhibited in-vitro antifungal activity against M. phaseolina (Chowdhury et al, 2015). As reported in previous studies, the synthesis and accumulation of OLPs depend on osmotic conditions, signifying its involvement in osmotic adaptations (Patade et al, 2013; Weber et al, 2014; Chowdhury et al, 2015). On the other hand a few reports have shown that osmotins and OLPs enhance tolerance to biotic stresses (Subramanyam et al, 2012; Vasavirama and Kirti, 2012; Choi et al, 2013), although the underlying biological mechanism remains unexplored.…”
Section: Introductionsupporting
confidence: 53%
“…Recently we have cloned and characterized a new OLP gene from Solanum nigrum ( SindOLP , BankIt 1588324 Solanum KC292261), which exhibited in-vitro antifungal activity against M. phaseolina (Chowdhury et al, 2015). As reported in previous studies, the synthesis and accumulation of OLPs depend on osmotic conditions, signifying its involvement in osmotic adaptations (Patade et al, 2013; Weber et al, 2014; Chowdhury et al, 2015). On the other hand a few reports have shown that osmotins and OLPs enhance tolerance to biotic stresses (Subramanyam et al, 2012; Vasavirama and Kirti, 2012; Choi et al, 2013), although the underlying biological mechanism remains unexplored.…”
Section: Introductionsupporting
confidence: 53%
“…In some cases, these endeavors have proven fruitful (Park et al, 2014;Weber et al, 2014). However, extensive genome content variation was observed between B73 and PH207 (3.4% of genes show genomic-level PAV).…”
Section: Discussionmentioning
confidence: 99%
“…The most traditional experimental approach uses plants grown in pots with soil (pot-based systems (PSys)) combined with a specific routine of watering. This system attempts to reproduce field conditions but requires careful physiological monitoring (StolfMoreira et al 2010b;de Paiva Rolla et al 2014;Mayer Weber et al 2014). Alternatively, water deficit can be mimicked using plants that are cultivated in hydroponic systems (HSys) combined with an abrupt water privation by removing the plant from the nutrition solution (Cowan 1965).…”
Section: Introductionmentioning
confidence: 98%